Software-enabled control : (IEEE Press,Wiley-Interscience, 2003)
Discusses open systems, object orientation, software agents, domain-specific languages, component architectures, as well as the dramatic IT-enabled improvements in memory, communication, and processing resources that are now available for sophisticated control algorithms to exploit. Useful for practitioners and researchers in the fields of real-time systems, aerospace engineering, embedded systems, and artificial intelligence.